2010
DOI: 10.1007/s00167-009-1034-3
|View full text |Cite
|
Sign up to set email alerts
|

Tumour-like lesions of the infrapatellar fat pad

Abstract: Three different tumour-like lesions within the infrapatellar fat pad, an osteochondroma, a localised pigmented villonodular synovitis and a synovial cyst are reported. The osteochondroma and the pigmented villonodular synovitis were treated by marginal excision, and the synovial cyst was resected using arthroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Rodriguez- Peralto et al ., [6] emphasize a possible metaplastic origin of the tumor, due to a traumatic event of Hoffa’s fat pad. Other authors [9, 13] reported a relation between this type of osteochondroma of the knee and a chronic impingement of the infrapatellar fat pad; they conclude that this lesion is the end-stage of Hoffa’s disease. Neither of our cases reported any history of significant trauma or symptomatic impingement of the infrapatellar fat pad, although both patients had noticed the mass many years before our first observation.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Rodriguez- Peralto et al ., [6] emphasize a possible metaplastic origin of the tumor, due to a traumatic event of Hoffa’s fat pad. Other authors [9, 13] reported a relation between this type of osteochondroma of the knee and a chronic impingement of the infrapatellar fat pad; they conclude that this lesion is the end-stage of Hoffa’s disease. Neither of our cases reported any history of significant trauma or symptomatic impingement of the infrapatellar fat pad, although both patients had noticed the mass many years before our first observation.…”
Section: Discussionmentioning
confidence: 91%
“…We believe that a biopsy is absolutely indicated when a significant diagnostic doubt exists. Magnetic resonance (MR) may be helpful for the diagnosis [8, 13], but in both our patients it was contraindicated, in one case owing to the presence of a pacemaker and in the other case for psychiatric problems.…”
Section: Discussionmentioning
confidence: 99%
“…Pathological involvement could be due to intrinsic factors or extrinsic factors. Intrinsic causes are due to primary pathology of HFP such as intracapsular chondroma,18 localized villonodular synovitis,19 post arthroscopy, shear injury, and post surgery 3. Extrinsic factors are synovial or intra-articular pathologies which secondarily involve HFP 320…”
Section: Discussionmentioning
confidence: 99%
“…Repetitive microtrauma leads to alteration in the metabolism of cells leading to release of vasoactive substances that sensitize synovium and fat tissue, causing necrosis of adipocytes 130. Fibrocartilagenous metaplasia of HFP was considered as the end stage of Hoffa's disease by many authors 17–19. Wicham et al .…”
Section: Discussionmentioning
confidence: 99%
“…It is considered that synovial osteochondroma rarely arises in the infrapatellar fat pad. Benign lesions have been treated by excision or marginal resection via arthrotomy [6-12]. In this case, we were able to identify the extent of the tumor on MRI and subsequently resect it under arthroscopic guidance.…”
Section: Discussionmentioning
confidence: 99%